An Appraisal of the Economic Potential of Mangrove Swamps - Nair, Mohd Yussof (1977)
Natural resources have always been in the centre of discussion since time immemorial. They are the basic building blocks of an economy just as amino acids are the basic building blocks of protein. One issue that has always been and will continue to be emphasized in future is the role of natural resources in the economic development of the country. In this respect the current preoccupation seems to be on the question of whether or not natural resources could be so managed as to support and subsequently contribute significantly to the development objectives of the country. Implicit in this is the issue of resource allocation. This study evaluates the economics of the present alternative uses of the mangrove swamp resource base in Sabah with the view of isolating an optimal combination of resource use that is consistent with Sabah state development priorities. Specifically, the relative contributions of each alternative with respect to income, employment and foreign exchange generations are determined and then compared. This study also investigates the present domestic consumption of fish and its future requirements relative to supply.The primary data source is a survey of two chip mills and five prawn factories in the state of Sabah in 1976. Supplemental data were obtained from published statistics. Essentially, the study employs two procedures--regression and partial investment criteria analysis. The former is used to determine the domestic consumption of fish, the derivation of production possibility curve and the maximum sustainable yield of fish landing. The latter is used to determine the trade off between the alternative uses. The study reveals that if income and foreign exchange earnings were given priorities, there is a strong case for conserving the mangrove resource base for prawn fishing industry rather than for chip production. However, the reverse situation would prevail if the objective was for employment generation. The study also shows that the future requirements of fish and fish products would exceed supply. The study concludes that given the present priorities in the state's development objective (i.e. bias in favour of income generation), it would be in the interest of the state to allocate the resource base in favour of the prawn fishing industry than in chip production. A more restrained felling of the mangrove trees is, therefore, suggested.